2009
DOI: 10.1016/j.jfa.2008.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Continuous model for homopolymers

Abstract: We consider the model for the distribution of a long homopolymer in a potential field. The typical shape of the polymer depends on the temperature parameter. We show that at a critical value of the temperature the transition occurs from a globular to an extended phase. For various values of the temperature, including those at or near the critical value, we consider the limiting behavior of the polymer when its size tends to infinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 6 publications
(12 reference statements)
0
73
0
2
Order By: Relevance
“…We point out that this kind of questions have been answered in depth in the case of the standard wetting model, that is formally in the a = 0 case, and that the problem of extending these results to the case where the defects are in a strip has been posed in [16], Chapter 2. Note that a closely related pinning model in continuous time has been considered and resolved in [10]; we stress however that their techniques are very peculiar to the continuous time setup. is an interface separating a dry zone from a wet zone.…”
Section: Definition Of the Modelmentioning
confidence: 99%
“…We point out that this kind of questions have been answered in depth in the case of the standard wetting model, that is formally in the a = 0 case, and that the problem of extending these results to the case where the defects are in a strip has been posed in [16], Chapter 2. Note that a closely related pinning model in continuous time has been considered and resolved in [10]; we stress however that their techniques are very peculiar to the continuous time setup. is an interface separating a dry zone from a wet zone.…”
Section: Definition Of the Modelmentioning
confidence: 99%
“…It is known , in the theory of BRWs the problem on the spectrum of a evolutionary operator of mean particle numbers plays an important role. Resolvent analysis of such operators (Cranston M. et al, 2009) has allowed to investigate BRWs with large deviation . The limit theorems on asymptotic behavior of the Green's function for transition probabilities were established.…”
Section: Ergodic Propertymentioning
confidence: 99%
“…Simon , Cranston et al , etc., considered the same problem for Brownian motion. They derived an exact asymptotic behavior of eμ(t,x) in case that μ is a nonnegative, continuous function with compact support.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they showed that the asymptotic behavior depends on the dimension d and is at most proportional to t . For α=2, Theorem is equivalent to the result of or .…”
Section: Introductionmentioning
confidence: 99%